Docentes en pandemia. Actitudes hacia las tecnologías y percepciones de la enseñanza virtual - Chiecher, Analía Claudia (Universidad de Costa Rica, 2022)
The article describes changes in attitudes towards ICT (Information and Communication Technologies) in university teachers. It contrasts two temporal moments: before and after the pandemic. It also describes positive and negative perceptions of teachers in relation to virtual teaching in the emergency context. Based on a mixed approach, both quantitative and qualitative data were collected and analyzed. The sample is made up of two groups of teachers (110 people), from different disciplinary areas and universities in Argentina. The data was collected through the administration of a self-report questionnaire, made up of 15 items related to attitudes towards ICT that required responses based on Likert scales. Additionally, 2 open-ended questions asked to mention positive and negative aspects of virtual teaching in emergencies. The results show changes in attitudes towards ICT, observing an evolution towards a more positive or optimistic vision of them. The teachers 'perceptions about virtual teaching highlighted its positive aspects, considering it as an enabler of pedagogical continuity, a promoter of students' self-regulation and favoring better time management. Among the negative aspects, the temporal dimension also emerged, mainly associated with the strong demand for planning, organization and effective regulation of time in virtuality. Likewise, the lack of contact between teachers and students, connectivity problems and the inability to carry out practical activities were also pointed out as negative aspects. The results are expected to represent valuable inputs for the design of educational practices in the new normal stage.